The effects of habitat complexity and hydraulic conditions on the establishment of benthic stream macroalgae - Tonetto, Aurelio Fajar [UNESP]; Cardoso-Leite, Ricardo [UNESP]; Peres, Cleto K.; Bispo, Pitágoras da Conceição [UNESP]; Branco, Ciro Cesar Zanini [UNESP] (Wiley-Blackwell, 2014)
1. Habitat complexity is thought to play an important role in various ecological communities, but its role under variable natural conditions is not well understood, particularly in lotic habitats where the complexity of the substratum influences the diversity and abundance of the benthic community.2. We investigated the effects of the habitat complexity of the substratum, as represented by fractal structure, on the establishment of stream macroalgae. We also analysed the influence of hydraulic conditions associated with variations in the fractal dimension of the substratum. We hypothesised that habitats with higher surface complexity would have higher macroalgal abundance and that hydraulic conditions would affect macroalgal establishment differently on surfaces of differing complexity.3. We designed a field experiment to elucidate the role of habitat complexity (represented by the fractal dimension and density of roughness elements) and consequent hydraulic conditions (assessed by the Reynolds number and drag forces) on algal growth. Sterile artificial substrata with five levels of complexity were placed in four unshaded streams. After 60 days of complete submergence, the substrata were removed from the streams, and the per cent cover of macroalgae was measured.4. We used a principal components analysis (PCA) to reduce the dimensionality and collinearity among our variables (fractal dimension, density of roughness elements, Reynolds number and drag force) and summarise them adequately. Axis 1 (PC1) values were used in a linear model to assess the relationship between the variables and macroalgal cover.5. PC1 explained 82.2% of the variability in substratum complexity and hydraulic condition. The fractal dimension and density of the roughness elements were negatively related with PC1, whereas the Reynolds number and drag force were related positively. Hydraulic conditions differed among each level of complexity, with the Reynolds number and drag force decreasing with increasing complexity. Macroalgal cover increased on surfaces with lower turbulence and drag force, indicating that less aggressive conditions are suitable for macroalgal colonisation. Additionally, the establishment of macroalgae was greatest on the leading edge of flat-top ridges, where the water velocity slows and the current changes direction.6. Habitat complexity and hydraulic conditions play an important role in the establishment of macroalgae in streams and could explain their naturally patchy distribution.
Keywords: habitat complexity; hydraulic conditions; stream macroalgae